Prevention of Nosocomial Infection through Application of Housekeeping - Qomariyatus Sholihah; Aprizal Satria Hanafi (Intelektual Pustaka Media Utama, 2017)
The hospital has a high risk of nosocomial infection. Nosocomial infection can infect patients in hospital and can inhibit the patient's recovery, even worsen a patient. The purpose of this study was to determine the relationship of the application of housekeeping with the total number of germs floor as prevention nosocomial infection in the treatment room Roses in Ulin Hospital Banjarmasin, Indonesia. The study design was observational analytic. The study population was all Roses class treatment rooms. The samples were taken from the floor germs 4 point class treatment rooms in hospitals Rose Ulin. Sampling was conducted in the first week and the second week in November 2015. Paired t-test results showed no relationship between the applications of housekeeping with the total number of germs floor with a p-value 0.015.This study found there was decreasing the total number of germ on the floor in all rooms. It is hoped that the hospital to continue to pay attention to the condition of the hospital, especially in terms of hygiene in order to avoid transmission of germs or nosocomial infections due to bacteria originating from the floor.